ALK fusion variants detection by targeted RNA-next generation sequencing and clinical responses to crizotinib in ALK-positive non-small cell lung cancer. (February 2018) - McLeer-Florin, Anne; Duruisseaux, Michael; Pinsolle, Julian; Dubourd, Sylvian; Mondet, Julie; Phillips Houlbracq, Mathilde; Magnat, Nelly; Fauré, Julien; Chatagnon, Amandine; de Fraipont, Florence; Giaj Levra, Matteo; Toffart, Anne-Claire; et al.
Highlights: RNA-seq has a good sensitivity and specificity compared to ALK IHC and FISH. RNA-seq is particularly useful when ALK IHC and FISH are equivocal/borderline. RNA-seq identifies fusion variants which likely modulate ALK inhibitors efficacy. Abstract: Objectives: The aim of the present study was firstly to assess in a clinical setting the yields of an amplicon-based parallel RNA sequencing (RNA-seq) assay for ALK fusion transcript variants detection in comparison with immunohistochemistry (IHC) and fluorescent in-situ hybridization (FISH) in a selected population of ALK-positive and ALK-negative non-small cell lung cancer (NSCLC) cases, and secondly to evaluate the impact of the ALK variant on crizotinib efficacy. Materials and methods: The cohort used for the assessment of the RNA-seq assay comprised 53 samples initially diagnosed as being ALK-positive based on the results obtained by IHC and/or FISH, and 23 ALK-negative samples. A distinction was made between 'truly' IHC/FISH positive or 'truly' IHC/FISH negative samples, and those for which the IHC and/or FISH were equivocal (IHC) or borderline-positive (FISH). Results: On the overall population, RNA-seq sensitivity (Se) and specificity (Spe) were of 80% and 100%, respectively when IHC and FISH were combined. For the 31 'truly positive' samples, Se and Spe of 100% were reached. An ALK status could be assigned by RNA-seq in 10/10 of the equivocal and/or borderline-positive IHC/FISH cases, 2/7 IHC/FISH discordant cases. When crizotinib efficacy was evaluated according to the type of ALK variant, better clinical outcomes were observed in crizotinib-treated patients with EML4-ALK v1/v2/others variants compared to v3a/b variants. Conclusion: RNA-seq detects ALK rearrangements with a high sensitivity and specificity using only 10 ng of RNA. It appears to be a promising rescue technique for non-clear-cut IHC/FISH cases and also offers a unique opportunity to identify ALK fusion variants and evaluate their predictive value for ALK inhibitors efficacy.